2005
DOI: 10.1063/1.1921359
|View full text |Cite
|
Sign up to set email alerts
|

Origin of transition metal clustering tendencies in GaAs based dilute magnetic semiconductors

Abstract: While isovalent doping of GaAs (e.g. by In) leads to a repulsion between the solute atoms, two Cr, Mn, or Fe atoms in GaAs are found to have lower energy than the well-separated pair, and hence attract each other. The strong bonding interaction between levels with t 2 symmetry on the transition metal (TM) atoms results in these atoms exhibiting a strong tendency to cluster.Using first-principles calculations, we show that this attraction is maximal for Cr, Mn and Fe while it is minimal for V. The difference is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Considering the difference between the solubility limit of Cr and Mn, this can be explained in terms of the tendency to cluster being stronger for GaAs doped with Cr than with Mn͑T c GaCrAs Ͼ T c GaMnAs ͒. This tendency was also shown earlier by the work of Mahadevan et al, 29 in which they showed that the pair and the four-body interaction energies are stronger for Cr in GaAs than for Mn in GaAs. Therefore, if one considers the same temperature, to have the same solubility limit for Cr and Mn, the strain applied in GaCrAs must be stronger than in GaMnAs.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Considering the difference between the solubility limit of Cr and Mn, this can be explained in terms of the tendency to cluster being stronger for GaAs doped with Cr than with Mn͑T c GaCrAs Ͼ T c GaMnAs ͒. This tendency was also shown earlier by the work of Mahadevan et al, 29 in which they showed that the pair and the four-body interaction energies are stronger for Cr in GaAs than for Mn in GaAs. Therefore, if one considers the same temperature, to have the same solubility limit for Cr and Mn, the strain applied in GaCrAs must be stronger than in GaMnAs.…”
Section: Resultssupporting
confidence: 53%
“…As already stated by other authors for the unstrained case, the mismatch of the lattice parameter of zincblende GaAs and MnAs, and consequently the resulting internal strain, is not the only responsible for the phase separation process, but there is also other factors, as unfavorable chemical interactions. 29 Mahadevan et al 29 studied the cluster tendencies in GaAs based MS, and obtained that the TM-TM pair interaction is stronger along ͓110͔ crystallographic direction. The authors also showed that the coupling between states with t 2 symmetry will be larger for two atoms occupying lattice positions along the zincblende bonding chain, lowering the energy of the system.…”
Section: Resultsmentioning
confidence: 99%
“…If, on the one hand, clustering tends to decrease the magnitude of the nearest-neighbor exchange, on the other hand it leads to the energetically most stable configuration; this is in agreement with recent results from calculations restricted to pairs of transition metals. 37 In Table II we display the energies of calculated ferromagnetic SQS configurations relative to the clustered one in which the three Mn atoms are first-nearest neighbors. We note that the SQS configurations labelled from 8 to 10, which have the highest total energies of the set, correspond to cases in which there are no first-neighbor pairs of Mn atoms.…”
Section: B Three Mn Atomsmentioning
confidence: 99%
“…This function could be, in principle, calculated if the spatial dependence of Mn-atoms interaction energy would be known. However, the exact reason for the tendency of Mn-atoms to clustering is unclear [16]. At the same time, Monte-Carlo calculations [17] show that impurity correlations have only small effects on the ferromagnetic transition temperature of Ga 1−x Mn x As 3D-system.…”
mentioning
confidence: 99%